Ultrasonic washing as an abiotic elicitor to induce the accumulation of phenolics of fresh-cut red cabbages: Effects on storage quality and microbial safety - Hong, Chen; Zhou, Hong-Chang; Zhao, Yi-Ming; Ma, Haile (Frontiers in Nutrition, 2022)
Ultrasonic washing has been proved to be an abiotic elicitor to induce the accumulation of phenolics in some fruit and vegetables. However, the feasibility of ultrasonic washing on the accumulation of phenolics in fresh-cut red cabbages has not yet been reported. Therefore, the effects of ultrasonic washing on the phenolics and related phenolic metabolism enzymes of fresh-cut red cabbages, as well as quality and microbial safety during cold storage, were investigated. Firstly, the single-factor tests were used to optimize the ultrasonic processing parameters, including frequency mode, frequency amplitude, power density, frequency cycle time, and ultrasonic washing. Then the activities of the enzymes related to phenolic metabolisms after optimal ultrasound treatment were investigated, including phenylalanine ammonia-lyase (PAL), polyphenol oxidase (PPO), and peroxidase (POD). Additionally, the quality and microbial safety of fresh-cut red cabbages stored at 4 ℃ under the optimal ultrasound treatment were evaluated. The results showed that the content of soluble phenolics (SPs) in fresh-cut red cabbages increased significantly during storage under the optimal conditions (28 ± 2 kHz, 60 W/L, 400 ms, and 20 min) compared with the control (P < 0.05). The PAL activity was activated, and the PPO and POD activities were inhibited after ultrasonic washing, which contributed to the increase in the content of SPs. Meanwhile, the storage quality and microbial safety of fresh-cut red cabbages were improved. Ultrasonic washing reduced the weight loss and respiration rate and improved the color and texture characteristics. Additionally, the fresh-cut red cabbages after ultrasonic washing showed more retention of ascorbic acid (AA), total soluble proteins (TSPs), total soluble sugars (TSSs), and total soluble solids (SSs) compared with the control. Finally, ultrasonic washing effectively inhibited the growth of bacteria, molds and yeasts, which is beneficial to the extension of the shelf-life of fresh-cut red cabbages. Therefore, ultrasonic washing can be used as a tool to increase the content of SPs in fresh-cut red cabbages while retaining quality attributes and microbial safety.